Islamic Law Overview of Mu'athah Buying and Selling at STIBA Makassar - Hamka, Baso; Wahid Haddade, Abdul; Ambo Masse, Abd. Rahman (International Journal of Islamic Studies, 2023)
This study aims to determine the practice of mu'athah buying and selling at STIBA Makassar and elaborate the procedures and laws for carrying out each mu'athah buying and selling transaction without any supervision from the seller. This study used a qualitative descriptive research method with a phenomenological approach. The data collection methods used were observation, interviews, and documentation. The data sources in this study were STIBA Makassar students, sellers of refilled water gallons, buyers, lecturers, and administrators as informants; the sources of primary data and documents in the form of data or tables of information as the secondary data. The results found a basis for the philosophy of mu'athah buying and selling, which existed during the period of the Prophet Muhammad and his companions until now because the ulama would not have different opinions regarding the law if mu'athah buying and selling transactions never existed. The practice of mu'athah buying and selling at STIBA Makassar often involves theft, and the suspect tends to return the thing during the fifth semester and above. The law of mu'athah buying and selling is permissible according to most ulama based on the evidence from the QS. Ali-Imran/3:41 and a hadith narrated by a Jewish enslaved people. The problem that occurs from the practice of buying and selling at STIBA Makassar is not due to problems with the contract, but there are problems out of the contract; when the vendible is often lost, it means that there is a theft and it is illegitimate.